Are Rawlsian Considerations of Corporate Governance Illiberal? A Reply to Singer - Blanc, Sandrine (Business ethics quarterly, 2016)
Singer has recently argued that questions related to corporate governance are beyond the reach of Rawls’s political conception of justice. This is because justice applies to the basic structure of society, understood as society’s legally coercive structures, and because corporate governance cannot be considered part of this structure in political liberalism. This commentary challenges the second part of the argument. First, it suggests that the criterion used to exclude corporate governance from the basic structure—whether employees can exit economic organizations—is not conclusive for corporate governance, notably as institutionalized in corporate law. Second, even if the focus were on corporate governance, it would still be possible to argue that it legally coerces citizens, if not employees, in a relevant way. Thus, the argument is not successful in demonstrating that political liberalism goes beyond its legitimate boundaries when considering that aspects of corporate governance may be matters of justice.